Transdermal clonidine in the treatment of severe hyperemesis. A pilot randomised control trial: CLONEMESI12. (1st April 2014) - Maina, A; Arrotta, M; Cicogna, L; Donvito, V; Mischinelli, M; Todros, T; Rivolo, S
<x xml:space="preserve">Abstract</x> Objective To study the efficacy of transdermal clonidine in the treatment of severe refractory hyperemesis gravidarum (HG), the most severe illness of pregnancy. Design The study had a randomised, double ‐blind, placebo‐controlled, cross‐over design (RCT). Setting Single tertiary referral hospital after admission of patients. Sample Twelve women of gestational age 6–12 weeks and a major grade of HG clinical severity who were unresponsive to standard antiemetic treatment. Methods The patients were randomly treated with and without the active drug (5 mg patch) for two consecutive periods of 5 days. The patients were allocated to a random list to receive first placebo and then active drug or the other way round. Other antiemetic drugs were administered on a scheduled or as‐needed basis. All patients received intravenous hydration and thiamine supplementation. Main outcome measures Pregnancy Unique Quantification of Emesis (PUQE) and visual analog scale (VAS) clinical scores, positive morning urine ketonuria, number of doses of standard antiemetic drugs required, and number of days off intravenous therapy were compared in the two periods. Results Transdermal clonidine led to a significantly greater improvement compared with placebo of the primary (PUQE score P = 0.026 CI 0.43–3.24; VAS score P = 0.010 CI 2.17–12.83) and secondary outcome measures. A reduction of blood pressure was reported for systolic 6 mmHg P = 0.01 and diastolic 3 mmHg P = 0.055. Conclusions This preliminary RCT demonstrates the efficacy of transdermal clonidine in the treatment of severe HG, leading to a significant reduction of symptoms and reducing the need for other supportive measures and medications.